DETERMINATION MODEL OF INDEPENDENT BUSINESS CREDIT "GRAMEENBANK" PATTERN USING SIMPLE ADDITIVE WAIGHTING (SAW) METHOD TO ENHANCING THE RURAL ECONOMIC DEVELOPMENT - Satria Abadi; Sri Hartati (Prosiding International conference on Information Technology and Business (ICITB), 2015)
This research aims to determine the aid creditprogram "grameenbank" by using Simple AdditiveWaighting (SAW) method in rural communities as aresource empowerment of rural women towardseconomic development of the region. The determinationof the criteria is to perfom the weight on theexisting.criteria which applied to the decisions making.The software program can generate customers wereselected as recipients grameenbank aid credit program.The Independent Business Credit system is a replicationof the pattern ofcredit 'Grameen Bank' (Meaning VillageBank developed in Bangladesh to serve the poor people)who have adapted their implementation inIndonesia. Credit package provided through thisinstitutional adjusted to the conditions and the ability oftheir poor, so that they are able to increase revenues andat the same time is able to be trusted because it can repayloans with discipline. These results indicate that theSimple Additive Waighting (SAW) method caneffectively help in the decision making and to determineprospective customers that receiver program in ruraldistricts Gemahripah Pringsewu. This programenhancing empowerment of rural women towardseconomic development of the region.Keywords: Grameen Bank, Simple AdditiveWaighting (SAW) Method